Pendampingan Penulisan Karya Ilmiah bagi Guru Berbasis Constructivist Approach di Sekolah Dasar Negeri - Budiarti, Erika Mei; Aziz, Abdullah Aminuddin; Sho Imah, Dewi Nurus; Azis, Ixora Chinensis (Universitas Negeri Malang, 2023)
This community service activity is carried out through the collaboration of the service team with partner institutions through the process of assisting in writing scientific papers to teachers in partner institutions (SDN Blimbing) that takes place effectively and efficiently. The pretest and postest results that were carried out during the mentoring, it can be seen that the process of mentoring activities for writing scientific papers is running successfully. Participants' understanding of the concept of scientific work, writing scientific articles, and searching for articles in internationally reputable journals has increased significantly. However, it still requires full assistance in writing articles, given the background of teachers who have never conducted research or even written scientific articles. Kegiatan pengabdian kepada masyarakat ini dilakukan melalui kerjasama tim pengabdian dengan lembaga mitra melalui proses pendampingan penulisan karya ilmiah kepada para guru di lingkungan lembaga mitra (SDN Blimbing) berlangsung secara efektif dan efisien. Hasil pretest dan postest yang dilakukan pada saat pendampingan, dapat diketahui bahwa proses kegiatan pendampingan penulisan karya ilmiah ini berjalan dengan sukses. Pemahaman peserta tentang konsep karya ilmiah, penulisan artikel ilmiah, serta penelusuran artikel pada jurnal bereputasi internasional mengalami peningkatan yang signifikan. Namun demikian masih memerlukan pendampingan penuh dalam pelaksanaan penulisan artikel, mengingat latar belakang guru yang memang belum pernah melakukan penelitian bahkan penulisan artikel ilmiah.